The Cultural Philosophy Values in The “Denpasar-Style Bridal Makeup: Symbols and Meanings” Documentary Film - Ni Kadek Dwiyani; I Kadek Puriartha; Dewa Ayu Leliana Sari (Institut Seni Indonesia Denpasar, 2023)
Documentary film is a film genre that has a very important role in human civilization. Documentary films can